Systematic review of MCDM approach applied to the medical case studies of COVID-19: trends, bibliographic analysis, challenges, motivations, recommendations, and future directions - Abdullah Hussein Abdullah Al-Amoodi (Tanjung Malim, 2023)
Systematic review of MCDM approach applied to the medical case studies of COVID-19: trends, bibliographic analysis, challenges, motivations, recommendations, and future directions by Abdullah Hussein Abdullah Al-Amoodi